ANALISIS KANOUNGAN FORMALIN PAOAIKAN ASIN (Oi Tempat Pelelangan Ikan Kecamatan Puger Kabupaten Jember 2014) - Anggara Aditia Pratama Putera; A. T Diana Nerawati; Nur Haidah (GEMA LINGKUNGAN KESEHATAN, 2015)
Formalin is used as disinfectant, preservative and is widely used in industries as a preservative for biologicalsamples, this substance should be banned from use as a food preservative. But in reality, formalin is used asa preservative in dried fish food for example. Continuous consumption of salted fish containing formalin cancause serious health problems such as cancer, central nervous system disorders, hypotension, diarrhea, heartdisorders, coma and even death.This is a descriptive study, aimed to describe the content of formaldehyde in salted fish sold in TPI Puger byassessing the physical quality of salted fish and performing laboratory tests for qualitative determination.Using simple random sampling technique, as much as 28 sampleswere obtained, consisted of dried fish soldby five vendors (A, B, E, G, J). Data analysis was done by correlating the physical condition of the salted fishidentified as containing formalin with results of descriptive laboratory test, and then compared with theMinister of Health Regulation No. 033 of 2012 on food additives.The results showed that 11 (39.2%) samples were indicated as containing formalin. Results of qualitative andquantitative laboratory tests on formalin content show that 11 samples were positive containingformaldehyde, the formaldehyde levels ranging from 1.1 ppm - 4.1 ppm. Types of salted fish containingformalin that is chicken feathers salted fish, nuts, Layur, manyung, lauro, Dorang and snapper.The study suggested the need for counseling to consumers and merchants by local health center about thedangers of consuming foods containing formalin, and provide education to the public through the media suchas by distributing posters or leaflets on good salted fish, salted fish containing formalin with its characteristics.The Department of Fisheries and Marine Resourcesneedsto cooperate with the local health center to provideroutine supervision to fish selling operation